Lexical noun phrase chunking with Universal Dependencies for Portuguese - de Souza, Aleksander Tomaz; Ruiz, Evandro Eduardo Seron (Anais do Simpósio Brasileiro de Tecnologia da Informação e da Linguagem Humana (STIL); 2023: Anais do XIV Simpósio Brasileiro de Tecnologia da Informação e da Linguagem HumanaDO - 10.5753/stil.2023.25482, 2023)
Partial parsing retrieves a limited amount of syntactic information from a sentence. This project describes the identification of a specific type of noun phrase, through partial syntactic analysis, defined as a lexical noun phrase (NP L ), in texts written in Brazilian Portuguese, and annotated according to the Universal Dependency (UD) formalism. The Transformation Based Learning algorithm, TBL–Brill, applied as baseline, obtained an accuracy of 87.42% considering the UD dependency relations and 91.44% considering the UD morphosyntactic tags. Two other classifiers, one based on binary trees and the other based on a decision forest, had inferior performance.